PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN HANDPHONE MEREK SAMSUNG JENIS ANDROID PADA MAHASISWA PENDIDIKAN EKONOMI FAKULTAS EKONOMI UNIVERSITAS NEGERI SURABAYA - ROSNADI, EDUK (Jurnal Pendidikan Tata Niaga (JPTN), 2014)
The need for communication devices such as mobile phones (cell phones) or smartphone it self always increase from year to year, especially Samsung android phone. This is because the consumption patterns of consumers at the moment that have always wanted an ease of communication that can support their daily activities. So many of the manufacturers of mobile phones increases sales with various advantages of mobile phones is one of the factors product quality and brand image. The purpose of this study was to determine whether the product quality and brand image influence on purchasing decisions Brand Samsung Android phone on Economic Education Students in the Faculty of Economics, University of Surabaya. This study used a quantitative approach. The population in this study were students majoring in Economic Education. Samples are taken of 127 respondents was determined using purposive sampling technique. Data Questionnaire collected with instruments. Data were analyzed using descriptive statistics. The study showed a significant effect ni partially to the quality of the product to the buying decision branded Samsung Android phone with indigo tcount 5,853 with a significance value of 0.000. As for the Brand Image nevertheless have a significant impact to the value tcountof 4.137 with a significance value of 0.000. While simultaneously, Product Quality and Brand Image shown positive results influence the purchasing decisions Brand Samsung Android phone and most dominant factor influencing the decision of the respondents are in the Brand Image. Keywords : Product Quality, Brand Image, Purchase Desicion Mobile Phone Brand Samsung Type Android